Identification and expression analysis of pineapple sugar transporters reveal their role in the development and environmental response - Fakher, Beenish; Jakada, Bello Hassan; Greaves, Joseph G.; Wang, Lulu; Niu, Xiaoping; Cheng, Yan; Zheng, Ping; Aslam, Mohammad; Qin, Yuan; Wang, Xiaomei (Frontiers in Plant Science, 2022)
In plants, sugars are required for several essential functions, including growth, storage, signaling, defense and reproduction. Sugar transporters carry out the controlled movement of sugars from source (leaves) to sink (fruits and roots) tissues and determine the overall development of the plant. Various types of sugar transporter families have been described in plants, including sucrose transporters (SUC/SUT), monosaccharide transporter (MST) and SWEET (from “Sugar Will Eventually be Exported Transporters”). However, the information about pineapple sugar transporters is minimal. This study systematically identified and classified 45 MST and 4 SUC/SUT genes in the pineapple genome. We found that the expression patterns of sugar transporter genes have a spatiotemporal expression in reproductive and vegetative tissues indicating their pivotal role in reproductive growth and development. Besides, different families of sugar transporters have a diel expression pattern in photosynthetic and non-photosynthetic tissues displaying circadian rhythm associated participation of sugar transporters in the CAM pathway. Moreover, regulation of the stress-related sugar transporters during cold stress indicates their contribution to cold tolerance in pineapple. Heterologous expression (yeast complementation assays) of sugar transporters in a mutant yeast strain suggested that SUT1/2 have the ability to transport sucrose, and STP13, STP26, pGlcT-L2 and TMT4 are able to transport glucose, whereas SWEET11/13 transport both sucrose and fructose. The information provided here would help researchers further explore the underlying molecular mechanism involved in the sugar metabolism of pineapple.